Consequences for selected high-elevation butterflies and moths from the spread of Pinus mugo into the alpine zone in the High Sudetes Mountains - Bílá, Karolína; Šipoš, Jan; Kindlmann, Pavel; Kuras, Tomáš (PeerJ, 2016)
Due to changes in the global climate, isolated alpine sites have become one of the most vulnerable habitats worldwide. The indigenous fauna in these habitats is threatened by an invasive species, dwarf pine (Pinus mugo), which is highly competitive and could be important in determining the composition of the invertebrate community. In this study, the association of species richness and abundance of butterflies with the extent of Pinus mugo cover at individual alpine sites was determined. Butterflies at alpine sites in the High Sudetes Mountains (Mts.) were sampled using Moericke yellow water traps. The results of a Canonical Correspondence Analysis (CCA) indicated that at a local scale the area of alpine habitats is the main limiting factor for native species of alpine butterflies. Butterfly assemblages are associated with distance to the tree-line with the optimum situated in the lower forest zone. In addition the CCA revealed that biotic factors (i.e. Pinus mugo and alpine tundra vegetation) accounted for a significant amount of the variability in species data. Regionally, the CCA identified that the species composition of butterflies and moths is associated with presence and origin of Pinus mugo. Our study provides evidence that the structure of the Lepidopteran fauna that formed during the postglacial period and also the present composition of species assemblages is associated with the presence of Pinus mugo. With global warming, Pinus mugo has the potential to spread further into alpine areas and negatively affect the local species communities.
Keywords: Alpine tundra; Central European mountains; Biodiversity loss; Postglacial development; Lepidoptera; Afforestation; Dwarf pine